Safety Aspects Of Andrographis Paniculata An Investigation Into Possible Male Reproductive Toxicity [RC658.5. A261 2005 f rb] [Microfiche 8664]. - Agarwal, Renu (2004)
Andrographis paniculata (AP) adalah salah satu bentuk terapi alternatif yang popular untuk penyakit diabetes di Malaysia.